Efek Spiritual Emotional Freedom Techniqueterhadap Cemas dan Depresi, Sindrom Koroner Akut - Derison Marsinova Bakara; Kusman Ibrahim; Aat Sriati (Faculty of Nursing Universitas Padjadjaran, 2013)
Sindrom koroner akut (SKA) merupakan penyakit jantung penyebab kematian. Gejala depresi, kecemasan, dan stres meningkat pada pasien SKA. Gejala ini dapat memengaruhi proses pengobatan dan penyembuhan serta menimbulkan komplikasi. Penelitian ini bertujuan untuk mengidentifikasi pengaruh SEFT terhadap penurunan gejala depresi, kecemasan, dan stres pada pasien SKA yang dirawat di ruang rawat intensif jantung. Rancangan penelitian menggunakan quasi eksperimen, teknik pengambilan sampel dengan consecutive sampling,sebanyak 42 orang. Penetapan jumlah responsden untuk kontrol dan kelompok intervensi menggunakan number ramdom trial, sehingga ditetapkan kelompok intervensi berjumlah 19 responsden dan untuk kelompok kontrol berjumlah 23 responsden. Kelompok intervensi dan kelompok kontrol diukur tingkat depresi, kecemasan, dan stres mengunakan kuesioner The Depression Anxiety Stres Scales 21(DASS 21) kemudian pada kelompok intervensi diberikan intervensi SEFT satu kali selama 15 menit dan diukur kembali tingkat depresi, kecemasan, dan stres pada kelompok intervensi dan kelompok kontrol. Data dianalisis dengan Wilcoxon dan Mann Whitney. Hasil menunjukkan perbedaan yang bermakna antara tingkat depresi, kecemasan, dan stres sebelum dan sesudah intervensi SEFT antara kelompok intervensi dan kelompok kontrol (p<0.05). Intervensi SEFT membantu menurunkan depresi, kecemasan, dan stres pada pasien SKA.Kata kunci:Depresi, intervensi SEFT, kecemasan, stresÃ‚Â AbstractAcute coronary syndrome (ACS) is a cause of heart disease deaths. Symptoms of depressi on anxiety, and stres is increased in patients with ACS. These symptoms may affect treatment and healing processand cause complications. This study aims to determine the effect of intervention Spiritual Emotional Freedom Technique (SEFT) to decrease depression, anxiety, and stres in patients with ACS who were treated in the cardiac intensive care unit. The research design was quasi-experimental, and using consequtive sampling as sampling technique, 42 responsdents were divided into intervention and control groups. Determination the number of responsdents for the control and intervention groups using a number ramdom trial, 19 responsdents intervention group and 23 responsdents the control group. Intervention group and control group measure levels of depression, anxiety, and stres using questionnaires The Depression Anxiety Stres Scales 21 (DASS 21) later in the intervention group was given SEFT intervention once for 15 minutes and measured return rates of depression, anxiety, and stres in the intervention group and the control group. Data were analyzed with the Wilcoxon and Mann Whitney. Results show significant differences between levels of depression, anxiety, and stres before and after the intervention SEFT between the intervention group and the control group (p<0.05). SEFT interventions help reduce depression, anxiety, and stres in patients with ACS. Limitations of this study is the difficulty in controlling the characteristics of the responsdents as a confounding variable. This research benefits that SEFT interventions can be used to reduce depression, anxiety, and stres in patients with ACS, and can be consider as one intervention.Key words: Anxiety, depression, stres, SEFT Intervention